The Use of Computer Based Diaries for the Assessment of Subjective Symptomatology - Tippett, L. O.; Zeleznick, L. D.; knowles, W. E. (Methods of Information in Medicine, 1975)
Better methods are needed to evaluate the therapy of diseases which are subject to frequent fluctuation in the intensity of symptoms and lack an objective measurement reflecting the disease state. A patient diary system is reported in which patient symptomatology is collected and the data computerized. The system provides for management and automated tabulation of large volumes of data. It has proved to be a successful way to obtain the detailed symptomatology data necessary to assess therapeutic regimens in hay fever clinical studies.
Keywords: Symptom Diary; Patient Diary; Hay Fever Therapy; Data Processing